Tumor-Activated TCRγδ+ T Cells from Gastric Cancer Patients Induce the Antitumor Immune Response of TCRαβ+ T Cells via Their Antigen-Presenting Cell-Like Effects - Chaoming Mao; Xiao Mou; Yuepeng Zhou; Guoyue Yuan; Chengcheng Xu; Hongli Liu; Tingting Zheng; Jia Tong; Shengjun Wang; Deyu Chen (Journal of Immunology Research)
Human γδ T cells display the principal characteristics of professional antigen-presenting cells (APCs), in addition to playing a vital role in immunity through cytokine secretion and their cytotoxic activity. However, it is not clear whether γδ T cells perform APC-like functions under pathological conditions. In this study, we showed that, in contrast to peripheral-derived γδ T cells directly isolated from PBMCs of gastric cancer patients, tumor-activated γδ T cells not only killed tumor cells efficiently but also strongly induced primary CD4+ and CD8+  αβ T cells proliferation and differentiation. More importantly, they abrogated the immunosuppression induced by CD4+CD25+ Treg cells and induced the cytotoxic function of CD8+  αβ T cells from patients with gastric cancer. In conclusion, tumor-activated γδ T cells can induce adaptive immune responses through their APC-like functions, and these cells may be a potentially useful tool in the development of tumor vaccines and immunotherapy.